Fuzzy Adaptive Control System of a Non-Stationary Plant; IOP Conference Series: Materials Science and Engineering; Vol. 142 : Innovative Technologies in Engineering - Nadezhdin I. S. Igor Sergeevich (2016, 2016)
Title screen